Development Of Blog “Hi Si IPA” On Ecosystem Materials To Improve Science Literacy For Students Grade V In Elementary School - Dini Rosyada Mahmud; Shirly Rizki Kusumaningrum; Radeni Sukma Indra Dewi (DIDAKTIKA: Jurnal Pendidikan Sekolah Dasar, 2022)
Learning media is an important part of the learning process. Students grade V need learning media blog to make it easier for understand learning material for theme ecosystems. Learning media blog has never been used in ecosystem materials in elementary school. The method used in this  research and development using five stages: the model ADDIE (Analysis-Design-Development-Implement-Evaluate). Quantitative data analysis use to process the data results in numbers obtained from filling out validation questionnaires by learning media experts and material experts. Qualitative data take from the suggestions and input of material experts, learning media experts, students, and teachers who perfected the learning media of the blog "Hai Si IPA". The result validation product learning media of the "Hai Si IPA" is 97%. So the  "Hai Si IPA" has an "Excellent" validity criterion. The first result validation blog material of the "Hai Si IPA" is  67% was in the "Good" category, so it needed to be revised. The second result validation is 83%. The material used in the learning media blog "Hai Si IPA" is "Very good." The advantages blog "Hai Si IPA" has an attractive design includes background, layout, images, quiz and animated videos so that students don't get bored easily using it and have their brand namely "Hai Si IPA". Keywords: Learning media, Blog, Science